1994
DOI: 10.1128/mcb.14.9.5961
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Cloning of a Receptor for BMP-2 and BMP-4 from NIH 3T3 Cells

Abstract: The bone morphogenetic proteins (BMPs) are a group of transforming growth factor ,B (TGF-Pi)-related factors whose only receptor identified to date is the product of the daf-4 gene from Caenorhabditis elegans. Mouse embryonic NIH 3T3 fibroblasts display high-affinity 125I-BMP-4 binding sites. Binding assays are not possible with the isoform 125I-BMP-2 unless the positively charged N-terminal sequence is removed to create a modified BMP-2, 125I-DR-BMP-2. Cross-competition experiments reveal that BMP-2 and BMP-4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
223
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(230 citation statements)
references
References 71 publications
(120 reference statements)
7
223
0
Order By: Relevance
“…2 This suggests that the BMP-2 signals are transduced by the complex of BMPR-IA and BMPR-II in these cells. It was reported that both BMPR-IA and BMPR-IB formed complexes with BMPR-II or DAF-4, a type II receptor for a homologue of BMP-2/BMP-4 in C. elegans, in a ligand-dependent manner when overexpressed together on the surface of COS cells (21,22,(25)(26)(27). In contrast to the truncated BMPR-IA, the kinase domain-truncated BMPR-IB did not inhibit the BMP-2 signaling in C2C12 cells even if its mRNA was abundantly expressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 This suggests that the BMP-2 signals are transduced by the complex of BMPR-IA and BMPR-II in these cells. It was reported that both BMPR-IA and BMPR-IB formed complexes with BMPR-II or DAF-4, a type II receptor for a homologue of BMP-2/BMP-4 in C. elegans, in a ligand-dependent manner when overexpressed together on the surface of COS cells (21,22,(25)(26)(27). In contrast to the truncated BMPR-IA, the kinase domain-truncated BMPR-IB did not inhibit the BMP-2 signaling in C2C12 cells even if its mRNA was abundantly expressed.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the type I receptor is conserved in all type I receptors of the TGF-␤ superfamily, suggesting that the BMP signals are transduced by the BMP type I receptor like those of TGF-␤. Two type I receptors (BMPR-IA and BMPR-IB) and one type II receptor (BMPR-II) have been identified for BMP-2 and BMP-4 (21)(22)(23)(24)(25)(26)(27). BMP-7 can interact with activin type I and type II receptors in addition to BMP-2/BMP-4 receptors (26,28).…”
mentioning
confidence: 99%
“…BMP signals are mediated by type II and type I serine/ threonine kinase receptors. Three type I receptors have been shown to bind BMP ligands, type IA and IB BMP receptors (BMPR-IA or ALK-3 and BMPR-IB or ALK-6) and type IA activin receptor (ActR-IA or ALK-2) (Koenig et al, 1994;ten Dijke et al, 1994;Macias-Silva et al, 1998). Three type II receptors for BMPs have also been identified and they are type II BMP receptor (BMPR-II) and type II and IIB activin receptors (ActR-II and ActR-IIB) (Yamashita et al, 1995;Nohno et al, 1995;Rosenzweig et al, 1995;Kawabata et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Physical binding studies employing IT-BMP-2 revealed dissociation constants, Kd, of 2-5 nM with the type I1 daf-4 receptor from Cuenorhubditis elegans (Estevez et al, 1993). Type I receptors expressed in COS cells, showed K,, values of 0.2-1 nM (Graff et al, 1994;Koenig et al, 1994;Penton et al, 1994;Yamaji et al, 1994). Binding affinities were found to be increased after cotransfection with daf-4 (Brummel et al, 1994).…”
mentioning
confidence: 99%